AB0217 Validity of Treat To Target Strategy for Comprehensive Disease Control in Chinese Patients with Rheumatoid Arthritis: A Real-World, Prospective Cohort Study. (15th July 2016) - Ma, J.; Wang, X.; Mo, Y.; Chen, L.; Dai, L.
Abstract : Background: The ultimate goal for rheumatoid arthritis (RA) management is comprehensive disease control (CDC) including clinical remission, normal physical function and non-radiographic progression. However, current recommendations suggest that decision and adjustment of RA therapy mainly bases on disease activity and adheres to the treat-to-target (T2T) strategy which target is remission or low disease activity (LDA). Little was known about the validity of T2T strategy in achieving CDC in real world practice. Objectives: To evaluate the validity and impact factors of T2T strategy in achieving CDC in Chinese RA patients. Methods: Patients with moderately to severely active RA (DAS28-ESR≥3.2) were recruited and treated according to T2T strategy and followed up at the 1st, 3rd, 6th, and 12th months. Clinical data was collected simultaneously at baseline and each visit. X-ray assessment of hand/wrist was repeated and scored according to modified total Sharp score (mTSS). Therapeutic target was remission (DAS28-ESR<2.6) or LDA (2.6≤DAS28-ESR<3.2). One-year CDC was defined as DAS28-ESR<2.6, HAQ score<0.5 and mTSS≤0.5. Results: (1) One hundred and three patients fulfilled 1-year follow-up. There were 33%, 48%, 57% and 56% patients achieved therapeutic target at the 1st, 3rd, 6th, 12th months respectively and 32% patients achieved CDC at the 12th month (Table 1 ). (2) Comparing with CDC-achieving group, the disease duration, baseline bony erosion and mTSS were significantly greater in CDC non-achieving group, while bDMARDs therapy was significantly less (all P <0.05). Further multivariate logistic regression analysis showed that bDMARDs therapy was a significant predictor of CDC-achieving (OR: 3.089, 95% CI: 1.255–7.600, P =0.008), while bony erosion at baseline was a significant predictor of CDC-non-achieving (OR: 4.392, 95%CI: 1.484–12.998, P =0.008). (3) The percentages of patients achieved clinical remission and normal physical function in CDC-achieving group were significantly higher than those in CDC-non-achieving group at the 1st, 3rd, 6th, 12th months respectively (all P <0.05). Univariate logistic regression analysis showed that remission and normal physical function at the 1st, 3rd, 6th were significant predictors of 1-year CDC (all P <0.05). Adjusted for bony erosion at baseline and bDMARDs therapy, multivariate logistic regression analysis showed that remission at the 3rd month (OR: 4.159, 95% CI: 1.647–10.506, P =0.003) and normal physical function at the 1st month (OR: 8.199, 95% CI: 2.078–32.340, P =0.003) predicted 1-year CDC. Conclusions: Our results implies only 32% patients achieved 1-year CDC under DAS28-based T2T strategy and the patients with baseline bony non-erosion, bDMARDs therapy and having rapid clinical and functional improvement within 3 months might be more likely to achieve 1-year CDC. Acknowledgement: This work was supported by National Natural Science Foundation of China (81471597), Specialized Research Fund for the Doctoral Program of Higher Education (20130171110075) and Guangdong Natural Science Foundation (2014A030313074). Disclosure of Interest: None declared